NORMA DAN NILAI DALAM ILMU EKONOMI ISLAM - adinugraha, hendri Hermawan (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2013)
Islam has been set up with the norms and values in each discipline of knowledge. Including Islamic economics, Islamic economics as a social science and theology are not only derived from the Quran and as-Sunnah, but also stems from empirical phenomena and economic problems in the field. Epistemologically, Islamic economics is divided into two disciplines: First, normative Islamic economics, which is the study of Islamic sharia laws relating to property affairs and treasures. Second, positive Islamic economics, which is the study of Islamic concepts relating to property affairs and treasures, especially with regard to the production of goods and services. Norms and values is created in Islamic economics aims to provide moral and ethical order in the economy itself, because it is basically the purpose of Islamic economics in the world is reaching the livelihoods and happiness in the Hereafter (hayatun thoyyibah and falah both in this world and in the hereafter).